The Influence of Kyai Leadership, Teacher Performance, and Parental Motivation on High School Students' Achievement Motivation at Islamic Boarding Schools - Taufik, Alwi; Ningsih, Eka Fitria; Setiawan, Agus; Hayati, Rina Mida; Choirudin, Choirudin (CV. Bimbingan Belajar Assyfa, 2025)
This study aims to analyze the influence of kyai leadership, teacher performance, and parental motivation on the achievement motivation of high school students in Islamic boarding schools (pesantren) in Kota Gajah District, Central Lampung Regency. A quantitative correlational approach was employed with a saturated sample of 127 students. The instrument was a Likert-scale questionnaire that had been tested for content validity (Aiken’s V), empirical validity (Pearson Product Moment), and reliability (Cronbach’s Alpha). Data were analyzed using simple and multiple linear regression with SPSS version 25. The results showed that: (1) kyai leadership had a positive and significant effect on achievement motivation (r = 0.528; R² = 27.9%); (2) teacher performance had a positive and significant but very small effect (r = 0.207; R² = 4.3%); (3) parental motivation had a positive and significant effect (r = 0.585; R² = 34.3%); (4) simultaneously, the three variables had a significant effect with a contribution of 48.2% (R = 0.694; R² = 0.482). These findings confirm that parental motivation is the strongest factor, followed by kyai leadership, while teacher performance contributes the least in the pesantren context. This study recommends strengthening the synergy of the three pillars of pesantren education.